Digital Book Model for Mangrove Ecotourism Development - I Gede Sujana Eka Putra (International Journal of Engineering and Emerging Technology, 2021)
The tourism sector is the sector most affected by the COVID-19 pandemic. Bali as one of the provinces that depends on the tourism sector, with economic growth in the third quarter of 2020 reaching -12.28%. One of the tourism sectors in Bali is the Kampoeng Kepiting mangrove ecotourism located in Tuban Village, Kuta - Badung District, which is developed and managed by the Wanasari fishing group. Kampoeng crab mangrove ecotourism offers several tour packages such as mangrove tours by canoe and boat, fishing, education, mangrove nurseries and planting, crab cage tours and culinary tours. Since its establishment in 2008 until before the pandemic, this ecotourism received tourist visits who wanted to enjoy the natural scenery of mangroves, culinary tours and mangrove education, but since the COVID 19 pandemic hit in 2020, this ecotourism began to lack visitors, impacting the economy of the fishing community. The research problem is how to design model of digital book to develop mangrove ecotourism. This research uses a descriptive qualitative method, to develop mangrove ecotourism by using digital book. This digital book is developed using the html and JavaScript web language, which is designed to improve web appearance as viewing information in a book. This ecotourism digital book can be accessed online, displaying the tour packages offered, information on tour packages and mangrove planting activities as an educational medium for mangrove conservation. The development of this digitalization model is expected to support the promotion of mangrove ecotourism during the COVID-19 pandemic.